The Influence Of Service Costs And Facilities On Student Acceptance Of The Institut Teknologi Dan Bisnis Bina Sarana Global - Wicaksono, Taufan Ardi; Amri, Mila; Arnie Mariana (Jurnal Ekonomi, 2024)
This research aims to determine the influence of costs and service facilities on student admissions at the Bina Sarana Global Institute of Technology and Business. Student Admissions is one of the routine activities carried out by all universities in Indonesia. There are several factors behind a person's decision to study at a university, including costs and service facilities.,. The research method used in this research is a quantitative method. The data collection method used in this research used a questionnaire. The data collection technique was carried out randomly. Data processing uses SPSS 25. Based on the results of this research, there is a significant influence on the influence of costs and service facilities on student admissions at the Bina Sarana Global Institute of Technology and Business, shown by the multiple linear regression equation Y = 2.429 + 0.482 X1 + 0.419 X2. The relationship between cost variables and facility variables on student acceptance variables is strong (R = 0.831).  Cost variables and facility variables simultaneously (together) influence the student acceptance variable by 69.1% and the remaining 30.9% is influenced by other factors.